Case Report: Beyond type 1 diabetes: a case of delayed MODY1 diagnosis and successful transition to sulfonylurea therapy - Gulisano, Chiara; Aloi, Concetta; Salina, Alessandro; Marazzi, Camilla; Spacco, Giordano; Cappato, Serena; Bocciardi, Renata; Iafusco, Dario; Tantari, Giacomo; d'Annunzio, Giuseppe; Minuto, Nicola; Maghnie, Mohamad; et al. (Frontiers in Medicine, 2025)
Maturity-onset diabetes of the young (MODY) is a rare, genetically heterogeneous form of diabetes characterized by early-onset dysglycaemia, typically before 25 years of age, and autosomal dominant inheritance. Among the different forms of MODY, HNF4A-MODY (MODY1) is caused by mutations in the HNF4A gene, which encodes a transcription factor essential for glucose metabolism. Here, we describe a novel splicing variant in the HNF4A gene (c.319+1G>A) identified in a 15-year-old girl with non-ketoacidotic diabetes and a family history of diabetes. Initially diagnosed with Type 1 diabetes (T1D), she required low insulin doses and displayed negative autoimmune markers. Genetic testing revealed the heterozygous variant inherited from her father and functional studies confirmed the variant's impact on splicing. Following the diagnosis of HNF4A-MODY, the patient's treatment was switched from insulin to sulfonylureas, resulting in improved glycaemic control and time in range, along with an improved quality of life. The report highlights the importance of considering MODY in young patients with diabetes who lack typical T1D characteristics and the value of combining clinical, genetic, and functional testing for accurate diagnosis and personalized treatment.